2021
DOI: 10.1177/1420326x211039546
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of COVID-19 indoor emissions from coughing and breathing with air conditioning and mask protection effects

Abstract: The COVID-19 infection has emerged as a disruptive pandemic at worldwide level. The study of the mechanism of contagion is one of the greatest challenges before a mass vaccination campaign that would protect populations. The study can support the development of knowledge and tools to develop possible strategies for containing its spread in future events. The saliva droplet aerosol expelled during breathing or coughing is the main cause for the propagation of the SARS-Cov-2. In this work, a URANS CFD approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…6,36,38 The rapid spreading of COVID-19 highlights the importance of better understanding of the dynamics and transmission routes of the expelled virus-laden droplets from these respiratory activities. 39,40 Inhalation Droplets or aerosols containing infectious pathogens inhaled by a susceptible person may cause infection. Inhalation route is considered as one important pathway of SARS-CoV-2 transmission as reported in the issued scientific brief by WHO on 30 April 2021.…”
Section: Exhalationmentioning
confidence: 99%
See 1 more Smart Citation
“…6,36,38 The rapid spreading of COVID-19 highlights the importance of better understanding of the dynamics and transmission routes of the expelled virus-laden droplets from these respiratory activities. 39,40 Inhalation Droplets or aerosols containing infectious pathogens inhaled by a susceptible person may cause infection. Inhalation route is considered as one important pathway of SARS-CoV-2 transmission as reported in the issued scientific brief by WHO on 30 April 2021.…”
Section: Exhalationmentioning
confidence: 99%
“…6,36,38 The rapid spreading of COVID-19 highlights the importance of better understanding of the dynamics and transmission routes of the expelled virus-laden droplets from these respiratory activities. 39,40…”
Section: Breathing Airflowmentioning
confidence: 99%
“…Research in the area of the spread of airborne diseases in enclosed environments has been done by researchers across the world. 8 It is essential for good research to become part of public policy as soon as possible. This is all the more essential in the COVID-19 pandemic when every step taken in the right direction for prevention of disease spread can save countless lives.…”
Section: The Indian Standard Code Is 9679 Titled As 'Code Ofmentioning
confidence: 99%
“…This phenomenon depends on many factors; the speed at which it is generated, whether we are in a closed or open place, anyhow there is a high-speed wind or a soft breeze, regardless there is ventilation, etc. In fact, the study by Cravero et al 17 , indicates that with adequate ventilation in an indoor environment completely changes the direction of exhaled flow. Stiti 15 has found that a particular 80 µm becomes solid waste before reaching the ground when the person exhaling it has a height of 1.6 m from the mouth to the ground.…”
Section: Introductionmentioning
confidence: 99%